Differential Diagnosis of Fulminant Myocarditis and Acute Coronary Syndromes in the Case of Failure of Coronary Angiography: A Case Report - Huang, Xiangfei; Gao, Yi; Hua, Fuzhou; Ying, Jun (Frontiers in Cardiovascular Medicine, 2021)
Fulminant myocarditis (FM) is a severe disease with a rapidly progressive and life-threatening course caused mainly by viral infection. The symptoms, laboratory findings, and presence of ECG changes resemble acute coronary syndrome. Therefore, coronary angiography is usually helpful in making the appropriate diagnosis. However, failure to obtain complete coronary artery images due to coronary artery anatomic variations poses a challenge for the diagnosis of FM. Here, we report a case of FM preliminarily diagnosed as acute coronary syndrome (ACS) due to the presence of coronary artery anomaly.